The right to identity and the action to establish paternity. - Sipán López, Maribel Janett (2017)
The purpose of this essay is to reflect on the application of the principle of the Best Interest of the Child when there are conflicts of interest or discrepancies of rights: a child’s right to identity v. the child’s right to legal paternity. The scientific and technological advances related to DNA genetic testing to prove paternal filiation and maternal filiation have put the issue of paternity of children conceived with a married woman and their recognition by a third party on the agenda, along with the provisions set forth under articles 396 and 404 of the Civil Code which preclude the possibility of challenging and/or declaring the paternity of a supposedly extramarital  child born within a marital relationship; and, on the other hand, the child’s right to identity according to the Principle of the Best Interest of the Child, in which the essential attributes of the person occupy an important place, as is the right to identity enshrined in Article 2, paragraph 1 of the Constitution, which includes the right to a name, to know one’s parents and to keep their surnames, as well as the right to a nationality and the obligation of the State to protect them. Consequently, principles regarding fundamental human rights such as the right to identity of a child and an adolescent, to the biological truth, to its biological origin, to its personality as they are established in the Convention on the Rights of the Child, in our Political Constitution, and in the Code of Children and Adolescents must prevail in relation to the already outdated articles mentioned in the Civil Code.